Susceptibility to hepatitis B virus infection in adults living in Spain - Soriano, Vicente; Aguilera, Antonio; Benito, Rafael; Gonzalez-Diez, Rocio; Miro, Elisenda; Liendo, Paloma; Rodriguez-Diaz, Juan Carlos; Cabezas, Teresa; Richart, Alberto; Ramos, José Manuel; Barea, Luisa; Alvarez, Carmen; et al. (Liver International, 2023)
BackgroundA protective hepatitis B virus (HBV) vaccine has been available for four decades. Universal HBV vaccination of infants is recommended by the WHO since the 1990s. Furthermore, HBV immunization is advised for all adults with high-risk behaviours and no seroprotection. However, HBV vaccine coverage remains globally suboptimal. The advent of new more efficacious trivalent HBV vaccines has renewed the interest in HBV vaccination. At present, the extent of current HBV susceptibility in adults remains unknown in Spain. MethodsHBV serological markers were assessed on a large and representative sample of adults in Spain, including blood donors and individuals belonging to high-risk groups. Serum HBsAg, anti-HBc and anti-HBs were tested in specimens collected during the last couple of years. ResultsFrom 13 859 consecutive adults tested at seven cities across the Spanish geography, overall 166 (1.2%) had positive HBsAg. Past HBV infection was recognized in 14% and prior vaccine immunization in 24%. Unexpectedly, 37% of blood donors and 63% of persons belonging to high-risk groups had no serum HBV markers and therefore were potentially HBV susceptible. ConclusionRoughly 60% of adults living in Spain seem to be HBV susceptible. Waning immunity might be more common than expected. Hence, HBV serological testing should be performed at least once in all adults regardless of risk exposures. HBV vaccine full courses or boosters should be administered to all adults lacking serological evidence of HBV protection.
Keywords: antibody waning; diagnosis; hepatitis B; prevention; public health; vaccine; JCR; Scopus